IDENTIFIKASI DAN ESTIMASI SUMBER DAYA BATUBARA MENGGUNAKAN METODE POLIGON BERDASARKAN INTEPRETASI DATA LOGGING PADA LAPANGAN ”ADA”, SUMATERA SELATAN - Deddi Adrian; Bagus Sapto Mulyatno (Engineering Faculty Universitas Lampung, 2018)
As petroleum reserves depleted, certainly encourage the government to search for new energy sources. Eksploration of coal is the right choice because its potential is so great in Indonesian especially in South Sumatera Province is known have content 37,80% from total resources in Indonesian. Well loggging method is one of geophysics method used to find and estimate coal resources. Advantages of well logging method is able to describe subsurface laterally. The purpose of this study is displaying an overview of subsurface rock layers, determine the direction of distribution by correlating coal seam between wells based on data logging, and to estimate coal resources in the research area. The total area of the author's research is 442.056 m2 has 10 wells. Log data used in this study is gamma ray log dan density log, where coal seams are characterized by gamma ray log response and low log density responses. On the field ”ADA” found four coal seam, that is seam A1 with thickness 8,28 m, seam A2 with thickness 13,62 m, seam B with thickness 18,50, and seam C with thickness 8,84. Direction of coal distribution from South to North with slope angle 5-30º and direction of sincerity from East to West. The author calculates the estimated coal resource using polygon method because this calculates method can be done with a short time and the results are right. Total coal by polygon method of 18.322.653 m3 in tons of 21.987.184–27.483.980 ton while calculations with software rock works 15 amount 18.786.254 m3 in tons of 22.543.505–28.179.381 ton.